"But I Don't Want to Tell Them the Answer": Preservice Teachers' (mis)understandings about literacy instruction. (August 2018) - Gelfuso, Andrea
Abstract: The purpose of this study was to notice and name the beliefs 33 preservice teachers had about literacy teaching/learning. The beliefs were noted by using evidence from their 'language-in-use' during supported, literacy planning sessions with a teacher educator. Critical discourse analysis revealed that the preservice teachers believed (1) assessment is instruction, (2) literacy teaching/learning is inauthentic, and (3) children are not intellectually motivated . The findings are discussed through the lenses of figured worlds and the apprenticeship of observation. Implications for teacher educators are offered. Highlights: Critical discourse analysis was used to bring beliefs to the fore. Preservice teachers believed that assessment is instruction. Preservice teachers believed that literacy teaching/learning is inauthentic. Preservice teachers believed that children are not intellectually motivated.